What Is the Role of AI in Pediatric Cardiology? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2015)
Artificial intelligence (AI) is rapidly transforming various fields of medicine, and pediatric cardiology is no exception. The integration of AI technologies...
Keywords: AI in Pediatrics; Pediatric; Cardiology; Artificial Intelligence; Machine Learning; Deep Learning; Medical Imaging